Pengaruh Kompensasi terhadap Kinerja Karyawan pada Dinas Ketenagakerjaan UPT Wilayah Sumatera Utara - Erina Yasmin; Saparuddin Siregar (Universitas Muhammadiyah Enrekang, 2022)
The focus of this study is on the Service of Manpower's UPT region I North Sumatra, specifically the impact of compensation on employee performance.At the Service of Manpower UPT region I North Sumatra, the goal of this study was to find out how compensation affects employee performance.In qualitative and subjective research methods, information is gathered through interviews and documentation.This study's findings demonstrate that the theory proposed by Amrullah is supported by research.At the UPT Service of Manpower Region I North Sumatra, the data indicate that compensation has a positive and very significant percentage effect on employee performance.The study's conclusion is that effective compensation demonstrates that UPT employees of the Service of Manpower Region I North Sumatra are more committed to the organization's goals and mission.